Scrotal Masson's tumour masquerading as dysplastic polyorchidism – a case report. Issue 4 (April 2022) - Lilis, Lydia; Wood, Fergus; Dickerson, David
Summary: This case describes a rare genitourinary presentation of a Masson's tumour, preoperatively assumed to be a dysplastic third testis.